The Impact of Litter Decomposition on Soil Organic Carbon Stability in Coastal Shelter Forests Under Thinning - ZHANG Zixu; HU Dingmeng; LU Yucun; WU Qicong; DONG Zhi; GAO Peng (Shuitu Baochi Xuebao)
[Objective] To elucidate the characteristics of litter decomposition and changes in soil organic carbon (SOC) fractions under thinning, and to reveal the impact of litter decomposition on the stability of SOC in coastal shelter forests under thinning. [Methods] After three years of thinning, the litter and surface soil (0—20 cm) of coastal shelter forests (Quercus acutissima Carruth. (QAC), Pinus thunbergii Parl. (PTP) and mixed Q. acutissima Carruth. and P. thunbergii Parl. (QP) in Qingdao were studied. In situ decomposition of litter, indoor analyses of chemical properties, and random forest model were used to characterize the litter decomposition and SOC fractions under three different thinning intensities (control 0, light 15% and heavy 30%), and analyzed their relationships. [Results] Heavy thinning significantly increased the mass remaining of QAC and QP litter during decomposition, with an increase of 22.36% and 4.18% compared to the control, respectively. The trend of K-value changes representing litter decomposition rate was opposite to mass remaining. The SOC content, mineral associated organic carbon (MAOC) content, and SOC stability of QAC and QP all significantly increased with the increase of thinning intensity. The content and stability of SOC were significantly correlated with nitrogen and phosphorus residual rates during litter decomposition under thinning, but not with litter decomposition rate. [Conclusion] Thinning reduces the decomposition rate of litter, but increases the residual rates of carbon, nitrogen, and phosphorus in litter, especially under heavy thinning. Thinning improves the stability of SOC, and the changes in SOC content and stability are mainly influenced by the residual rates of nitrogen and phosphorus in litter, with phosphorus residual rate having the greatest impact.